Modeling and simulation of transverse wakefields in PWFA. (July 2020) - Chen, J B B; Schulte, D; Adli, E
Abstract: A simplified model describing the PWFA (plasma wakefield acceleration) transverse instability in the form of a wake function parameterized only with an effective cavity aperture radius a is benchmarked against PIC-simulations. This wake function implies a 1/a 4 scaling of the transverse wakefields, which indicates transverse intra-beam wakefields typically several orders of magnitude higher than in conventional acceleration structures. Furthermore, the wakefield formalism is utilized to perform a parameter study for a 1.5 TeV plasma wakefield accelerator, where the constraint on drive beam to main beam efficiency imposed by transverse wakefields is taken into account. Eventually, a parameter set with promising properties in terms of energy spread, stability and luminosity per power was found.